Perioperative Profile of Stand-Alone Cages in Anterior Cervical Discectomy and Fusion for Degenerative Cervical Stenosis: Reduced Bleeding and Hospital Stay Compared to Cage-Plate Constructs - Handi Suntama Effendy; Rendra Leonas; Debby Handayati Harahap (Sriwijaya Journal of Surgery, 2025)
Introduction: Anterior cervical discectomy and fusion (ACDF) is a common surgical treatment for degenerative cervical stenosis. Stand-alone cages (SAC) and cage-plate constructs (CPA) are frequently used, with comparable reported fusion rates. This study aimed to compare the perioperative profiles, specifically intraoperative bleeding and length of hospital stay, alongside fusion rates, between ACDF-SAC and ACDF-CPA for single-level degenerative subaxial cervical stenosis in an Indonesian population. Methods: A retrospective cohort study was conducted using medical records from February to March 2025, including patients who underwent single-level ACDF-SAC or ACDF-CPA for degenerative subaxial cervical stenosis between June 2022 and June 2024 at Dr. Mohammad Hoesin General Hospital, Palembang. Twenty-one patients (10 ACDF-SAC, 11 ACDF-CPA) were included. Data on demographics, operative level, intraoperative bleeding, length of hospital stay, and 6-month fusion rates were analyzed. Results: No significant differences were observed in age (p=0.056), gender (p=0.635), or BMI (p=0.708) between groups. The ACDF-CPA group had significantly more procedures at the C5-6 level (p=0.010). Intraoperative bleeding was significantly lower in the ACDF-SAC group (86.90 ± 30.00 cc) compared to ACDF-CPA (183.27 ± 58.74 cc; p=0.000). Length of hospital stay was shorter for ACDF-SAC (4.70 ± 1.49 days) versus ACDF-CPA (6.27 ± 1.19 days; p=0.015). Fusion rates were 100% for ACDF-SAC and 90.9% for ACDF-CPA (RR=2.000; 95% CI 1.290–3.100; p=1.000), a non-statistically significant difference. The single non-fusion occurred at C3-4 in the ACDF-CPA group. Conclusion: In patients undergoing single-level ACDF for degenerative subaxial cervical stenosis, the use of stand-alone cages was associated with significantly less intraoperative bleeding and shorter hospital stays compared to cage-plate constructs, without compromising 6-month fusion rates. These findings suggest potential perioperative advantages for the ACDF-SAC technique.